2009
DOI: 10.1186/ar2605
|View full text |Cite
|
Sign up to set email alerts
|

Antirheumatic drug response signatures in human chondrocytes: potential molecular targets to stimulate cartilage regeneration

Abstract: Introduction Rheumatoid arthritis (RA) leads to progressive destruction of articular cartilage. This study aimed to disclose major mechanisms of antirheumatic drug action on human chondrocytes and to reveal marker and pharmacological target genes that are involved in cartilage dysfunction and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 45 publications
0
46
0
1
Order By: Relevance
“…Previous studies have shown that EGCG decreased the expression of COX-2 [23] and mPGES [15] . However, the exact mechanism of the inhibi- Figure 6).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have shown that EGCG decreased the expression of COX-2 [23] and mPGES [15] . However, the exact mechanism of the inhibi- Figure 6).…”
Section: Discussionmentioning
confidence: 86%
“…After showing that PGE 2 stimulated HepG2 cell growth and knowing that mPGES expression is inhibited by EGCG [15] , we aimed to determine the inhibitory effect of EGCG (12.5−100 μg/mL) on the production of PGE 2 in HCC cell lines. EGCG inhibited PGE 2 production as compared with controls (cells treated with serum-free DMEM).…”
Section: Egcg Inhibits Pge 2 Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt to identify key marker genes termed molecular signatures in chondrocytes that are involved in expression of catabolic mediators (inflammatory mediators, cytokines, chemokines and matrix destructive enzymes) and anabolic mediators (matrix synthesis, proliferation and differentiation) was undertaken by Andreas et al (2009). Of 110 RA-related genes identified in human chondrocyte cultures (derived from knees of post-mortem subjects), the expression of those genes controlling key enzymes was markedly reduced by non-cytotoxic concentrations of azathioprine, sodium aurothiomalate and methotrexate but less so by CQ, while the NSAIDs, diclofenac and piroxicam affected genes expressing inflammation (NFjB) and chemokines/cytokines.…”
Section: H-chloroquine Uptake By Bovine Nasal Cartilage In Presence Amentioning
confidence: 99%
“…127 A preliminary analysis of key regulatory molecules as measured by antibody-based protein membrane arrays that were associated with cartilage destruction, included IL-6, CCL2, CXCL1-3, IL-8/CXCL8, whereas a genome-wide microarray analysis of human chondrocytes stimulated by the SF from RA patients included adenosine A2A receptor, COX-2, TLR-2, spermine synthase, receptor-interacting serine-threonine kinase-2, CXCL1, CXCL8, CCL20, CXCR4, IL-1β, IL-6, as well as MMP-10 (stromelysin-2) and MMP-12 (human macrophage elastase). 129 A second study by Andreas et al 129 identified additional novel genes that appeared to be part of the signature of inflamed synovium in RA, including connective tissue growth factor (CTGF), CXCR7, IL-23A, TNFAIP-2 and TXNIP, to name only a few. A similar analysis performed on inflamed synovium from OA patients could provide evidence for common gene expressional events that link RA to OA disease progression.…”
mentioning
confidence: 99%